South Asian Free Trade Area and food trade: Implications for regional food security - Megan Ward; Hansjörg Herr; Jennifer Pédussel Wu (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2020)
This paper explores the impact of the South Asian Free Trade Area (SAFTA) agreement on food security by using a gravity model to examine the regional changes in trade in agricultural products. This is followed by a discussion of how this might affect the four dimensions of food security, availability, access, stability and utility. While coordination between SAFTA members has provided some positive food security attainment, institutional uncertainty and conflicts have prevented the full potential benefits from being reached.
Keywords: F02; F1; F15; O13; Q18; 330; International Trade; Food Security; South Asia Free Trade Area; Development; Agriculture